Management of Thoracic Outlet Syndrome with a Sympathetic Presentation. - Rivera, Oliver; Griffin, Kristina (Orthopedic Physical Therapy Practice, 2024)
Background and Purpose: Thoracic outlet syndrome (TOS) and T4 syndrome can present with similar clinical findings through different pathoanatomical and pathophysiological means. This case report describes the management of a patient diagnosed with TOS with a sympathetic presentation. Methods: A 31-year-old male presented with a 2-year history of upper extremity pain and paresthesias, temperature changes, discoloration, and neck pain after increasing exercise frequency. Two episodes of discoloration in all extremities with subjective "heart racing" sensation lasting less than 5 minutes were also reported. Clinical Findings: A positive venogram for venous TOS was reported. Objective examination demonstrated positive TOS testing, limited thoracic and first rib mobility, and skin temperature fluctuation and discoloration after a push-up task. A thoracic manipulation to T4 resulted in resolve of skin temperature fluctuation. Clinical Relevance: A thorough subjective and objective examination was necessary to navigate this patient's presentation, evaluate the findings, and consider interventions. Sympathetic symptoms are often due to a thoracic dysfunction and management with thoracic manipulation should be considered. Conclusion: A patient presenting with skin temperature fluctuation after a push-up task resolved symptoms after thoracic manipulation.